Pasteurella multocida Non-Native Joint Infection after a Dog Lick: A Case Report Describing a Complicated Two-Stage Revision and a Comprehensive Review of the Literature - Lam Philip W; Andrea V Page (Canadian Journal of Infectious Diseases and Medical Microbiology)
Prosthetic joint infections (PJIs) are commonly caused by pathogens such as Staphylococcus aureus and coagulase-negative staphylococci; however, other microbial etiologies and specific risk factors are increasingly recognized. Pasteurella multocida is a Gram-negative coccobacillus that is part of the normal oral flora in many animals, and is particularly common in dogs and cats. PJIs caused by P multocida have been reported only rarely in the literature and typically occur in the context of an animal bite or scratch. The present article describes a P multocida joint infection that occurred after a dog lick and complicated a two-stage revision arthroplasty. A comprehensive review of the literature regarding P multocida PJIs follows.